After the Pied Piper - Lidin, Konstantin (project baikal, 2015)
The age segregation becomes reality in today's urbanistics. There are cities and settlements in which there is absolutely no youth, only people of ‘the third age’. The tendency to carry university campuses out of city borders can lead to expansion of an age segregation practice. It is possible to assume that in the process of ‘eviction’ of youth from the city, it will become more conservative, less tolerant and less vital. In different years several projects of Irkutsk State (classical) University campus were proposed assuming location of the campus within the city structure. Recently there have been ideas to locate the campus outside the city line. When discussing options of campus location, it is necessary to consider possible effects of "deyouthification" of the city.
Keywords: campus; age segregation; third age; social psychology; urbanistics